2022
DOI: 10.3390/f13010084
|View full text |Cite
|
Sign up to set email alerts
|

Rolling Shear Properties of Cross-Laminated Timber Made from Australian Plantation Eucalyptus nitens under Planar Shear Test

Abstract: With the increasing availability of fast-growing Eucalyptus plantation logs in Australia in recent years, the timber manufacturing sector has become interested in discovering the opportunities of producing value-added timber products from this resource. Cross-laminated timber (CLT) could be a potential sustainable product recovered from this resource and supply material for commercial buildings. Shear of the inner cross-laminates, known as rolling shear, is one of the governing factors in serviceability and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Currently, several studies are being conducted to analyze the feasibility of using hardwoods in the production of CLT panels. These studies aim to evaluate the applicability of foreign species in homogeneous (Aicher et al 2016a;Ehrhart and Brandner 2018;Espinoza and Buehlmann 2018;Corpataux et al 2020;Ettelaei et al 2021;Ettelaei et al 2022;Nero et al 2022;Das et al 2023;Gutierrez et al 2023;Wang et al 2018) and hybrid panels (Aicher et al 2016b;Ma et al 2021;Hematabadi et al 2021;Srivaro et al 2022). The research regarding the application and mechanical properties of Brazilian native woods is still scarce, despite recent studies related to the topic (Silva et al 2023).Brazil has a large availability of these species, which could be an excellent alternative for this type of product.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several studies are being conducted to analyze the feasibility of using hardwoods in the production of CLT panels. These studies aim to evaluate the applicability of foreign species in homogeneous (Aicher et al 2016a;Ehrhart and Brandner 2018;Espinoza and Buehlmann 2018;Corpataux et al 2020;Ettelaei et al 2021;Ettelaei et al 2022;Nero et al 2022;Das et al 2023;Gutierrez et al 2023;Wang et al 2018) and hybrid panels (Aicher et al 2016b;Ma et al 2021;Hematabadi et al 2021;Srivaro et al 2022). The research regarding the application and mechanical properties of Brazilian native woods is still scarce, despite recent studies related to the topic (Silva et al 2023).Brazil has a large availability of these species, which could be an excellent alternative for this type of product.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-laminated timber (CLT) is one option for utilising fibre-managed E. nitens feedstocks because the orthogonal layup can potentially offer more uniform physical and mechanical properties and reduce the effect of individual SPFs [5]. Pangh et al [6] conducted pioneering research to determine the bending properties of CLT derived from Eucalyptus plantations.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings, including the modulus of elasticity (MOE) and modulus of rupture (MOR), suggested the potential utilisation of Eucalyptus plantations in CLT applications. Subsequently, Ettelaei et al [5] investigated rolling shear properties on heterogeneous E. nitens CLT samples under the Planar Shear Test. The results demonstrated that the performance of heterogeneous E. nitens CLT was satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that most of the aforementioned research focused on the RS properties of CLT panels produced from European and North American timber species. Some recent studies reported RS properties of CLT panels produced from Australian radiata pine and New Zealand Douglas fir [18,19,32] and Australian Plantation Eucalyptus nitens [33]. However, no previous study has investigated the RS properties of CLT feedstock boards from commercially available Australian softwoods such as southern, hoop and radiata pine and examine the impact of various factors on RS properties.…”
Section: Introductionmentioning
confidence: 99%